Analisis Pengaruh Gaya Kepemimpinan Transaksional dan Gaya Komunikasi terhadap Komitmen Organisasi pada Kantor Sekretariat DPRD Kabupaten Konawe Utara - Azis, Azis; Razak, Abdul; Nur, Muh (Indo-Fintech Intellectuals: Journal of Economics and Business, 2023)
This study aims to determine and analyze the influence of transactional leadership style and communication style on organizational commitment at the Secretariat Office of the North Konawe Regency DPRD. The sample in this study consists of all employees at the Secretariat Office of the North Konawe Regency DPRD, totaling 65 people. This research uses multiple linear regression analysis. The results of the study indicate that: (1) Transactional leadership style and communication style have a positive and significant influence on the organizational commitment of employees at the Secretariat Office of the North Konawe Regency DPRD. (2) Transactional leadership style has a positive and significant influence on the organizational commitment of employees at the Secretariat Office of the North Konawe Regency DPRD. (3) Communication style has a positive and significant influence on the organizational commitment of employees at the Secretariat Office of the North Konawe Regency DPRD.